Two new species of Syndicus in southern India (Coleoptera, Staphylinidae, Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2023)
To date, five species of the Australo-Oriental genus Syndicus Motschulsky have been discovered in India, although the true distribution of one of them (the type species of the genus) remains unclear, as the only known specimen comes from “Indes orientales”, a large historical area that also included territories outside the Indian subcontinent. Two new species are described: Syndicus (s. str.) microphthalmus sp. n., the first known Syndicus with strongly reduced eyes; and Syndicus (Semisyndicus) primus sp. n., the first Indian member of the subgenus Semisyndicus. An updated key to identification of Syndicus of India is given.